Application of the method of finite elements in the process of mathematical modeling in urology - V. M. Popkov; D. Yu. Potapov; A. N. Ponukalin; B. I. Blumberg (Бюллетень сибирской медицины, 2012)
The article presents data on possibility of the application of the method of finite elements (FEM) in the mathematical modeling of various diseases of the organs of the urogenital system, their diagnostics and treatment. Special attention was paid to the prospects of application of FEM for modelling methods of surgical treatment of diseases of the kidneys and urinary tract.